Money In The Eyes Of Sufism: Insights From An Indonesian Tariqat - Irawan, Bambang; Zahriani, Nurul (International Journal Labs, 2024)
Money has historically been used as a means of oppression, personal gain, and manipulation in politics, law, and justice, often contributing to societal discord. This article examines the concept of money and its societal perceptions through the lens of Prof. Dr. H. Kadirun Yahya, a prominent Indonesian Sufi and Mursyid of the Tariqah Naqshbandiyah, known for his success in managing a wide range of business ventures. Utilizing qualitative research methods, including interviews, observation, and documentation, the study investigates Yahya's numerous business initiatives aimed at fostering prosperity. These initiatives span diverse sectors such as agribusiness, including large-scale plantations (oil palm, apple, orange, and other crops), livestock farming (poultry, fish, ducks, goats, and cows), and enterprises in furniture manufacturing, workshops, drinking water factories, electronics, travel services, and more. The findings highlight Yahya's belief that money serves as a manifestation of divine light, a tool for attaining blessings and life's necessities. While money lacks inherent value, it remains essential for human existence. His view, consistent with other Sufi teachings, likes money to a mirror that reflects various possibilities based on its use. Grounded in Sufi principles that emphasize unity, illumination, and divine manifestation, Yahya argues that money should be employed to combat injustice, dishonesty, and exploitation. Its ultimate purpose is to uphold morality, promote social justice, equitable wealth distribution, and meet basic human needs. This research underscores the importance of further studies on integrating Sufi values into business management.